Concrete micro-crack fog vaporization repair material and repair method
The A, B and C powder are atomized into tiny droplets or aerosols through the mist vaporization device. The synergistic effect of the negative pressure air extraction device and sealing coatings is used to solve the problem of insufficient penetration depth and distribution uniformity of slurry in the repair of micro-cracks of concrete, and the comprehensive repair and strength enhancement of the deep cracks are achieved.
Patent Information
- Application Number
- CN202411869981.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The prior art has problems of insufficient slurry penetration depth and distribution uniformity in the repair of concrete microcracks, and it is difficult to ensure the comprehensive restoration of the deep cracks.
A concrete micro-crack mist vaporization repair material, including liquid A, liquid B and powder C, is used to atomize these materials into tiny droplets or aerosols through the mist vaporization device. The synergistic effect of the negative pressure air extraction device and sealing paint is used to achieve deep penetration and uniform distribution of the repair material.
It effectively improves the penetration depth of the slurry, ensures that the repair liquid fully covers the inside of the crack, especially the deep part, enhances the repair effect, ensures that the inside of the crack is uniformly repaired, and enhances the crack strength.
Smart Images

Figure CN119797822A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete crack repair, and in particular to a concrete micro-crack mist vaporization repair material and a preparation and use method thereof. Background Art
[0002] During long-term use, concrete often develops cracks due to temperature changes, loads or other factors. If these cracks are not repaired in time, they will lead to the penetration of external factors such as water and chemicals, causing further damage to the concrete and even affecting the stability of the structure.
[0003] At present, traditional concrete crack repair methods mostly rely on liquid perfusion or cementitious material injection, but these methods have certain limitations in penetration depth and reaction uniformity, especially for micro cracks with an opening less than 0.3 mm, it is difficult to ensure comprehensive repair of the deep cracks.
[0004] Microbial induced calcium carbonate precipitation (MICP) repair technology is a new concrete crack repair method that repairs cracks by producing calcium carbonate precipitation through the metabolism of microorganisms. However, this technology also faces the problem of insufficient slurry penetration depth and distribution uniformity in practical applications.
[0005] Therefore, how to optimize the injection and distribution of slurry, especially how to effectively inject slurry into deep cracks, becomes the key to improving the repair effect. Summary of the invention
[0006] The purpose of the present invention is to solve the shortcomings of the prior art and propose a concrete micro-crack mist vaporization repair material and its preparation and use method. The present invention is not only suitable for repairing micro-cracks in tunnel lining concrete, but also can be used in various fields such as civil engineering and water conservancy projects where permeability repair is required, such as repairing concrete micro-cracks in dams, bridges, etc.
[0007] A concrete micro-crack mist vaporization repair material comprises liquid A, liquid B and powder C; wherein liquid A is an aqueous solution containing urease bacteria, or a sodium alginate solution containing urease bacteria, or a sodium alginate-nanofiber solution containing urease bacteria; liquid B is a mixed solution of calcium ion and urea solution, wherein the calcium ion concentration is 1-2 mol / L and the urea concentration is 1-3 mol / L; and powder C is a microencapsulated repair agent.
[0008] Preferably, the calcium source is calcium acetate or calcium chloride.
[0009] Preferably, the urease-containing bacteria in liquid A are Bacillus pasteurianus and / or Micrococcus urea, and the urease activity in liquid A is 50-60 mmol / (L·min).
[0010] Preferably, the sodium alginate solution containing urease bacteria is obtained by adding urease bacteria liquid into sodium alginate aqueous solution and mixing, and the final mass fraction of sodium alginate is 0.25-2.5%.
[0011] Preferably, the sodium alginate-nanofiber solution containing urease bacteria is obtained by adding urease bacteria solution into an aqueous solution containing sodium alginate and nanofibers, and the final mass fraction of sodium alginate is 0.25-2.5%, and the final mass fraction of nanofibers is 0.25-2.5%.
[0012] Preferably, the nanofibers are cellulose nanofibers.
[0013] Preferably, liquid A further contains: Clostridium butyricum and Saccharomyces cerevisiae; the ratio of the number of live bacteria of Clostridium butyricum, Saccharomyces cerevisiae to that of urease-containing bacteria is 1-2:1-2:2-4.
[0014] The present invention adds Clostridium butyricum and Saccharomyces cerevisiae to the urease bacterial solution, which can promote the MICP process to a certain extent through synergistic metabolism, regulating microenvironment, providing templates and other approaches. First, the metabolites produced by Clostridium butyricum and Saccharomyces cerevisiae can provide a carbon source, and the carbon dioxide released by metabolism can reduce the pH value of alkaline concrete to a certain extent, creating favorable conditions for the growth of urease bacteria. Second, the carbon dioxide released by metabolism also helps to increase the concentration of carbonate ions, which is conducive to the precipitation of calcium carbonate. The cell surfaces of yeast and Clostridium butyricum may have certain electrical charges or biomacromolecules (such as polysaccharides, proteins), which can be used as crystal nucleation templates to promote the nucleation and deposition of calcium carbonate on the microbial surface. Third, the mixed bacterial system may form synergistic metabolism, such as yeast can provide biologically active substances such as vitamins and amino acids to promote the activity of urease bacteria.
[0015] Preferably, C powder is a microencapsulated repair agent.
[0016] Preferably, the mass ratio of liquid A, liquid B and powder C is 1:1:0.2-0.4. Specifically, in the following repair process, the mass ratio of liquid A mist vaporized droplets, liquid B mist vaporized droplets and powder C atomized aerosol is 1:1:0.2-0.4.
[0017] Preferably, the microencapsulated repair agent is prepared by the following steps: fly ash, potassium feldspar, sodium silicate and sodium aluminate are mixed, wet-ground and granulated to obtain a core material; amino-terminated polyamide amine and polyethylene glycol are added to a solvent and stirred evenly, the core material is added thereto and mixed evenly, and spray-dried.
[0018] The present invention uses fly ash compounded with potassium feldspar, sodium silicate and sodium aluminate, and atomizes and dries the fly ash to form a microencapsulation process on the surface. After atomization, the fly ash forms an aerosol that evenly enters the cracks, and has good affinity with the sodium alginate and nanofibers in liquid A, producing a synergistic effect to effectively fill the cracks and effectively enhance the crack strength. In the presence of water, the fly ash reacts with potassium feldspar, sodium silicate and sodium aluminate and expands, and cooperates with microorganisms to repair the cracks, which not only has a fast repair response, but also can ensure the effective filling of the cracks. At the same time, the crack interface structure is dense, and the product has excellent mechanical properties and excellent durability.
[0019] Preferably, the mass ratio of fly ash, potassium feldspar, sodium silicate, sodium aluminate, amino-terminated polyamidoamine and polyethylene glycol is 10-20: 1-5: 1-2: 1-2: 0.1-1: 1-2.
[0020] Preferably, the particle size of the core material is 50-100 μm.
[0021] A method for repairing concrete micro-cracks by mist vaporization comprises the following steps: fitting a sealing cover of a mist vaporization device and an exhaust cover of an exhaust device tightly to both ends of a concrete crack respectively; applying a sealing coating to the concrete cracks not covered by the sealing cover or the exhaust cover; mist vaporization device is used to mist vaporize liquid A, liquid B and powder C of the concrete micro-crack mist vaporization repair material, and the exhaust device performs exhaust treatment at the same time, so that the tiny droplets or aerosols obtained by the mist vaporization treatment fully cover the cross-sectional surface of the concrete crack due to pressure difference and convection.
[0022] After being atomized, C powder forms an aerosol with a particle size of 100-150μm, which can be stably suspended in the cracks and evenly diffused with air convection, achieving uniform distribution and deep penetration of the repair material; and the aerosol dissolves when it meets water in the cracks, releasing active ingredients, undergoing chemical reactions to form sediments, and then filling and repairing the cracks within a certain period of time.
[0023] The number and distribution of the mist vaporization nozzles of the mist vaporization device can be adjusted according to the distribution of the crack network. When the crack network distribution range is wide (diameter greater than 2m) or the number of cracks within a 2m diameter range exceeds 5, additional mist vaporization nozzles are required. Generally, a circle with a diameter of 2m is a repair unit (one repair unit contains one mist vaporization nozzle).
[0024] The mist vaporization device is one of a pneumatic mist vaporization device (10-100 μm), a mechanical mist vaporization device (20-200 μm) or an ultrasonic mist vaporization device (0.1-10 μm). Different mist vaporization devices produce different diameters of mist vaporization droplets, which can be suitable for repairing cracks of different openings.
[0025] In the lining crack network, ultrasonic mist vaporization device can be used for micro cracks with an average crack opening of less than 0.1mm, ultrasonic mist vaporization device or pneumatic mist vaporization device can be used for micro cracks with an average crack opening of 0.1mm-0.3mm, and pneumatic mist vaporization device or mechanical mist vaporization device can be used for cracks with an average crack opening greater than 0.3mm.
[0026] The sealing hood and the exhaust hood are tightly fitted to the concrete surface through silicone pads and silicone adhesives to prevent the mist vaporized slurry from leaking out.
[0027] Beneficial effects:
[0028] 1. The present invention can effectively improve the penetration depth of the slurry through the synergistic effect of the mist vaporization device, the negative pressure exhaust device and the sealing coating, ensuring that the repair liquid fully covers the inside of the crack, especially the deep part.
[0029] 2. The mist vaporized liquid A and liquid B of the present invention can be better mixed and reacted in the cracks to generate more calcium carbonate precipitation, thereby enhancing the repair effect.
[0030] 3. Clostridium butyricum and Saccharomyces cerevisiae in liquid A can promote the MICP process to a certain extent through synergistic metabolism, regulating the microenvironment, providing templates, etc. The microencapsulated repair agent used in powder C achieves dense, high-strength and efficient repair of cracks through multiple mechanisms such as physical filling, chemical reaction, coating and slow release, and toughening and reinforcement.
[0031] 4. The present invention utilizes a sealing cover to effectively prevent the leakage of mist vaporized slurry, reduce waste, and improve grouting efficiency. The repair liquid is evenly distributed in the form of tiny droplets or aerosols, ensuring that the inside of the cracks are evenly repaired. In particular, the aerosol formed by the atomization of C powder has a smaller particle size and higher suspension stability, and can penetrate deep into tiny cracks, making up for the shortcomings of traditional slurries or tiny droplets in terms of permeability, ensuring that the repair material is fully in contact with the crack wall, evenly covering and promoting the occurrence of calcium carbonate precipitation reaction.
[0032] 5. This method is not only suitable for repairing concrete micro cracks, but can also be used in various projects such as civil engineering and water conservancy that require permeability repair, such as repairing concrete micro cracks in dams and bridges. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 Schematic diagram of the microstructure of the repair product obtained by the method of the present invention; wherein (a) is a schematic diagram of the microstructure of the mist vaporization repair process; and (b) is a schematic diagram of the microstructure of the repair product.
[0034] Figure 2This is a schematic diagram of the concrete micro-crack mist vaporization repair method proposed in the present invention, that is, a schematic diagram of using the concrete micro-crack mist vaporization repair method proposed in the present invention to repair the vertical crack at A in the tunnel; wherein the arrow indicates the direction of mist vapor flow.
[0035] Figure 3 Schematic diagram of the combination of the sealing cover / exhaust cover and the crack.
[0036] Figure 4 Schematic diagram of the mist vaporization device.
[0037] Figure 2-Figure 4 In the figure, 1 is a mist vaporization device, 2 is an exhaust device, 3 is a sealing area of a sealing coating, 4 is a silicone pad, 5 is a silicone adhesive, 11 is a sealing cover, 12 is a mist vaporization switch, 13 is a container filled with liquid A, 14 is a container filled with liquid B, 15 is a container filled with powder C, and 21 is an exhaust hood.
[0038] Figure 5 This is a comparison chart of relative permeability coefficients after repairing standard concrete specimens with cracks using the repair materials and repair methods obtained in Example 1, Example 6 and Comparative Examples 1-3.
[0039] Figure 6 A comparison chart of the compressive strength recovery rate and the flexural strength recovery rate after repair of each group is shown in FIG. 1 for repairing a standard concrete specimen with cracks using the repair materials and repair methods obtained in Example 1, Example 6 and Comparative Examples 1-3. DETAILED DESCRIPTION
[0040] The present invention will be further explained below in conjunction with specific embodiments.
[0041] Example 1
[0042] A concrete micro-crack mist vaporization repair material comprises liquid A, liquid B and powder C.
[0043] Among them, liquid A is a Bacillus pasteurianus solution, and the urease activity in liquid A is 60mmol / (L·min); liquid B is a mixture of calcium acetate and urea solution, with a calcium ion concentration of 1.2mol / L and a urea concentration of 1.8mol / L.
[0044] C powder is a microencapsulated repair agent. The microencapsulated repair agent is prepared by the following steps: 30g fly ash, 6g potassium feldspar, 3g sodium silicate, and 3g sodium aluminate are mixed evenly, anhydrous ethanol is added for wet grinding, and granulation is performed to obtain a core material with an average particle size of 70μm; 1g amino-terminated polyamidoamine and 3g polyethylene glycol 600 are added to 160g anhydrous ethanol and stirred evenly, the core material is added thereto, mixed evenly, and spray dried.
[0045] A method for repairing concrete micro-cracks by mist vaporization, comprising the following steps:
[0046] The outside of the mist vaporization nozzle is sealed with a sealing cover, which fits tightly with the crack surface to form a closed space to prevent the mist vaporization slurry from leaking out;
[0047] A vacuum device is installed at the other end of the crack network to extract air and create a negative pressure environment (-10kPa); the negative pressure value is adjusted according to the depth and width of the crack to maintain air convection inside the crack and promote the penetration of slurry; a micron-level filtration device is used to collect liquid for secondary mist vaporization repair;
[0048] Nearby extended cracks are sealed with paint to ensure that the entire crack network has only a mist and vapor sealing hood as an inlet and an exhaust hood as an outlet;
[0049] Store liquid A, liquid B and powder C in separate containers respectively, select a suitable mist vaporization device according to the actual crack width, and adjust the nozzle's spray pressure and liquid flow rate to ensure the fineness and uniformity of the droplets; open the mist vaporization nozzles of the three containers at the same time, and perform mist vaporization repair for 5 days. Liquid A, liquid B and powder C are mixed and sprayed into the cracks to react and generate calcium carbonate and other sediments to fill the cracks and repair them.
[0050] For cracks with an opening of 0.1-0.3mm, an ultrasonic mist vaporization device is used with a flow rate controlled at 50mL / min. The particle size of the mist vaporized droplets of liquid A and liquid B is 0.1-10μm, and that of the C powder atomized aerosol is 100-150μm. The mass ratio of the A liquid mist vaporized droplets, the B liquid mist vaporized droplets and the C powder atomized aerosol is 1:1:0.3.
[0051] Example 2
[0052] The difference from Example 1 is that the solution A in this example is a sodium alginate solution containing Bacillus pasteurianus, and the final mass fraction of the sodium alginate is 1.5%.
[0053] Example 3
[0054] The difference from Example 1 is that the microencapsulated repair agent of this example is prepared by the following steps: 10g of fly ash, 1g of potassium feldspar, 1g of sodium silicate, and 1g of sodium aluminate are mixed, wet-ground, and granulated to obtain a core material with an average particle size of 80 μm; 0.1g of amino-terminated polyamide amine and 1g of polyethylene glycol are added to the solvent and stirred evenly, the core material is added thereto, mixed evenly, and spray-dried.
[0055] Example 4
[0056] The difference from Example 1 is that the solution A in this example is a sodium alginate-cellulose nanofiber solution containing Bacillus pasteurianus, the final mass fraction of sodium alginate is 1.5%, and the final mass fraction of cellulose nanofiber is 1.5%.
[0057] Example 5
[0058] The difference from Example 1 is that the solution A in this example is a sodium alginate-cellulose nanofiber solution containing Bacillus pasteurianus and Micrococcus urea. The final mass fraction of sodium alginate is 1.5%, the final mass fraction of cellulose nanofiber is 1.5%, and the urease activity is 60 mmol / (L·min).
[0059] Example 6
[0060] The difference from Example 1 is that the solution A in this example is a sodium alginate-cellulose nanofiber solution containing composite bacteria.
[0061] In liquid A, the composite bacteria include: Bacillus pasteurianus, Micrococcus urea, Clostridium butyricum, and Saccharomyces cerevisiae. The ratio of the number of live bacteria of Bacillus pasteurianus, Micrococcus urea, Clostridium butyricum, and Saccharomyces cerevisiae is 3.5:0.5:1:1.
[0062] The urease activity in solution A is 60 mmol / (L·min), the final mass fraction of sodium alginate is 1.5%, and the final mass fraction of cellulose nanofibers is 1.5%.
[0063] Comparative Example 1
[0064] Different from Example 1, in this comparative example, during the mist vaporization repair, the mist vaporization nozzles of the A liquid container, the B liquid container and the C powder container alternately perform mist vaporization (the mist vaporization nozzle of the A liquid container is turned on for 6 hours, and the mist vaporization nozzles of the B liquid and C powder containers are turned off; then the mist vaporization nozzle of the A liquid container is turned off, and the mist vaporization nozzles of the B liquid and C powder containers are turned on for 6 hours). The total mist vaporization time is 5 days.
[0065] Comparative Example 2
[0066] The difference from Example 6 is that the microencapsulated repair agent in this comparative example is prepared by the following steps: 30g of fly ash, 6g of potassium feldspar, 3g of sodium silicate, and 3g of sodium aluminate are stirred evenly, anhydrous ethanol is added for wet grinding, and granulation is performed to obtain a core material with a particle size of 70μm; 3g of polyethylene glycol 600 is added to 160g of anhydrous ethanol and stirred evenly, the core material is added thereto, mixed evenly, and spray dried.
[0067] Comparative Example 3
[0068] The difference from Example 6 is that the composite bacteria in this comparative example include: Bacillus pasteurianus, Micrococcus urea and Saccharomyces cerevisiae, and the ratio of the number of live bacteria of Bacillus pasteurianus, Micrococcus urea and Saccharomyces cerevisiae is 3.5:0.5:2.
[0069] Put 900g of standard cement into a mixing pot, add 1350g of standard sand evenly during low-speed mixing, then add 450g of water and stir at low speed for 5s, then at high speed for 15s; pour into a test mold, vibrate for 30s, stop, remove the test mold, scrape off the mortar that protrudes from the test mold and smooth the surface. Mark the test mold and send it to a curing box for natural curing for 28 days to obtain a standard concrete sample.
[0070] After random sampling, initial compressive strength and flexural strength tests were carried out, and then the remaining samples were lightly pressed using a pressure testing machine to cause cracks (while using a fixture to maintain the same crack width), with a preload speed of 0.1 mm / min and a pressure value of 60% of the ultimate compressive strength.
[0071] The initial permeability coefficient (k0) of the above-mentioned standard concrete specimens with cracks was measured, and specimens with similar initial permeability coefficients were selected. The standard concrete specimens with cracks were repaired using the repair materials and repair methods obtained in Example 1, Example 6 and Comparative Examples 1-3.
[0072] The permeability coefficient (k) of each group of repaired samples was measured again, and the relative permeability coefficient (k / k0) was calculated; then the compressive strength and flexural strength of each group of samples after repair were tested, and the compressive strength recovery rate and flexural strength recovery rate after repair were calculated.
[0073] Recovery rate of compressive strength after repair = compressive strength after repair ÷ initial compressive strength × 100%
[0074] Restoration rate of flexural strength after repair = Restoration flexural strength ÷ initial flexural strength × 100%
[0075] like Figure 5 and Figure 6 As shown, after repair using the repair material and repair method obtained in Example 6, the relative permeability coefficient is the smallest, and the recovery rate of compressive strength and the recovery rate of flexural strength after repair are the highest, which are better than the other groups (P < 0.05).
[0076] The applicant believes that this is because the present invention can effectively improve the penetration depth of the slurry through the synergistic effect of the mist vaporization device, the negative pressure exhaust device and the sealing coating, ensuring that the repair liquid fully covers the inside of the crack, especially the deep part; and the mist vaporized A liquid and B liquid are evenly distributed in the form of tiny droplets or aerosols, and can better mix and react in the cracks to generate more calcium carbonate precipitation, ensuring that the inside of the cracks are evenly repaired and enhancing the repair effect. Moreover, Clostridium butyricum and Saccharomyces cerevisiae in liquid A can promote the MICP process to a certain extent through synergistic metabolism, regulating the microenvironment, providing templates and other means. The microencapsulated repair agent used in C powder achieves dense, high-strength and efficient repair of cracks through multiple mechanisms such as physical filling, chemical reaction, coating slow release and toughening and reinforcement. The present invention uses a sealing cover to effectively prevent the leakage of mist vaporized slurry, reduce waste, and improve grouting efficiency. The repair liquid is evenly distributed in the form of tiny droplets or aerosols to ensure that the inside of the cracks are evenly repaired. In particular, the aerosol formed by the atomization of C powder has a smaller particle size and higher suspension stability, and can penetrate deep into micro cracks, making up for the shortcomings of traditional slurries or tiny droplets in terms of permeability, ensuring that the repair material is in full contact with the crack wall, evenly covering and promoting the precipitation reaction of calcium carbonate. This method is not only suitable for the repair of concrete micro cracks, but also can be used in various projects such as civil engineering and water conservancy that require permeability repair, such as dams, bridges, etc. The repair response is fast, and the cracks can be effectively filled. The crack interface structure is dense, and the product has excellent mechanical properties and durability.
[0077] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A concrete micro-crack mist vaporization repair material, characterized in that: Includes A liquid, B liquid and C powder; Wherein, liquid A is an aqueous solution containing urease bacteria, or a sodium alginate solution containing urease bacteria, or a sodium alginate-nanofiber solution containing urease bacteria; Solution B is a mixture of calcium ion and urea solution, with a calcium ion concentration of 1-2 mol / L, a urea concentration of 1-3 mol / L, and a calcium source of calcium acetate or calcium chloride. C powder is a microencapsulated repair agent.
2. The concrete micro-crack mist vaporization repair material according to claim 1, characterized in that: The urease-producing bacteria in liquid A are Bacillus pasteurianus and / or Micrococcus urea, and the urease activity in liquid A is 50-60 mmol / (L·min).
3. The concrete micro-crack mist vaporization repair material according to claim 1, characterized in that: Liquid A also contains: Clostridium butyricum and Saccharomyces cerevisiae; the ratio of the number of live bacteria of Clostridium butyricum, Saccharomyces cerevisiae and urease-containing bacteria is 1-2:1-2:2-4.
4. The concrete micro-crack mist vaporization repair material according to claim 1, characterized in that: The sodium alginate solution containing urease bacteria is obtained by adding urease bacteria liquid into sodium alginate aqueous solution and mixing, and the final mass fraction of sodium alginate is 0.25-2.5%; The sodium alginate-nanofiber solution containing urease bacteria is obtained by adding urease bacteria solution into aqueous solution containing sodium alginate and nanofibers, wherein the final mass fraction of sodium alginate is 0.25-2.5% and the final mass fraction of nanofibers is 0.25-2.5%.
5. The concrete micro-crack mist vaporization repair material according to claim 1, characterized in that: The microencapsulated repair agent is prepared by the following steps: fly ash, potassium feldspar, sodium silicate and sodium aluminate are mixed, wet-ground and granulated to obtain a core material; amino-terminated polyamide amine and polyethylene glycol are added to a solvent and stirred evenly, the core material is added thereto and mixed evenly, and spray-dried.
6. The concrete micro-crack mist vaporization repair material according to claim 5, characterized in that: The mass ratio of fly ash, potassium feldspar, sodium silicate, sodium aluminate, amino-terminated polyamidoamine and polyethylene glycol is 10-20: 1-5: 1-2: 1-2: 0.1-1: 1-2.
7. The concrete micro-crack mist vaporization repair material according to claim 1, characterized in that: The mass ratio of liquid A, liquid B and powder C is 1:1:0.2-0.
4.
8. A method for repairing concrete micro-cracks by mist vaporization, characterized in that: The method comprises the following steps: fitting the sealing cover of the mist vaporization device and the exhaust cover of the exhaust device tightly to the two ends of the concrete crack respectively; and applying the sealing coating to the concrete crack not covered by the sealing cover or the exhaust cover; A mist vaporization device is used to mist vaporize the liquid A, liquid B and powder C of the concrete micro-crack mist vaporization repair material as claimed in any one of claims 1 to 7 to form tiny droplets or aerosols; At the same time, the vacuum device performs vacuum processing, so that the tiny droplets or aerosols fully cover the cross-sectional surface of the concrete crack due to pressure difference and convection.
9. The method for repairing concrete micro-cracks by mist vaporization according to claim 8, characterized in that: After atomization, C powder forms an aerosol with a particle size of 100-150μm.
Citation Information
Patent Citations
Method for blocking cracks of airport cement concrete pavement
CN107299577A
Concrete for shielding radiation
CN111807778A
Joint mortar for improving durability of new and old concrete joint surface
CN114873965A
Biological material for rapidly repairing concrete microcracks and preparation method thereof
CN115626790A
Magnetic microbial repairing material for repairing concrete cracks and preparation method thereof
CN117623672A
Cited By
Device and method for actively repairing microcracks on surface of iced water concrete structure
CN120649692A